Producing organic fish and mint in an aquaponic system - Saleem Mustafa; Normala Wahap; Abentin Estim; Yong, Annita,Seok Kian; Shigeharu Senoo (2010)
Aquaponics combines aquaculture and hydroponics to grow fish and plants together in one integrated system. The waste produced by fish serves as manure for the plants and water cleaned this way is made available to fish through recirculation. With the right choice of fish and plant species, aquaponics serves as a model of environmentally compatible and sustainable food production.